2022
DOI: 10.1007/s10856-022-06706-y
|View full text |Cite
|
Sign up to set email alerts
|

Silk fibroin microgels as a platform for cell microencapsulation

Abstract: Cell microencapsulation has been utilized for years as a means of cell shielding from the external environment while facilitating the transport of gases, general metabolites, and secretory bioactive molecules at once. In this light, hydrogels may support the structural integrity and functionality of encapsulated biologics whereas ensuring cell viability and function and releasing potential therapeutic factors once in situ. In this work, we describe a straightforward strategy to fabricate silk fibroin (SF) micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…VEGF levels were found to increase up to 22 pg mL −1 by day 7. Similar to a previous work, the shape and size were well maintained, thus meaning that SF microgels are stable and can exchange metabolites [51] . It is evident from the above-mentioned studies that SF is an excellent candidate for cell encapsulation for cell structural and functional preservation.…”
Section: Sf Hydrogel As Delivery Vehiclesupporting
confidence: 82%
See 1 more Smart Citation
“…VEGF levels were found to increase up to 22 pg mL −1 by day 7. Similar to a previous work, the shape and size were well maintained, thus meaning that SF microgels are stable and can exchange metabolites [51] . It is evident from the above-mentioned studies that SF is an excellent candidate for cell encapsulation for cell structural and functional preservation.…”
Section: Sf Hydrogel As Delivery Vehiclesupporting
confidence: 82%
“…Bono et al used ultrasonification to fabricated 200 µm microgels in a water-oil emulsion phase to encapsulate cells. [51] Applying shear force through vortexing impels molecule-molecule interactions to form a gel [52] . To decrease the pH, an electric field is applied across the solution for silk to agglomerate [53] .…”
Section: Methodsmentioning
confidence: 99%
“…Tan et al showed that a microfluidic, microgel fabrication system could be coupled with a microgel‐trapping device to provide a fixed microarray system that can be later selectively retrieved depending on desired expression 202,203 . While microgels made with microfluidics can be highly uniform, they require a high level of expertise for use, and thus simpler dropwise methods could be of interest 204–206 …”
Section: Three‐dimensional High Throughput Culture Systemsmentioning
confidence: 99%
“… 202 , 203 While microgels made with microfluidics can be highly uniform, they require a high level of expertise for use, and thus simpler dropwise methods could be of interest. 204 , 205 , 206 …”
Section: Three‐dimensional High Throughput Culture Systemsmentioning
confidence: 99%
“…Among numerous candidates for single-cell encapsulation, silk fibroin (SF), a natural protein-based biomaterial derived from Bombyx mori silkworm cocoons, stands out as a promising biomaterial due to its desirable biological and physical properties, including biocompatibility, mild immunogenicity, mechanical properties, manipulability, and biodegradability. , Additionally, SF preserves cell viability, proliferation, and other vital functionalities after encapsulation while enhancing their stiffness and resistance to external mechanical perturbations. , Mechanical properties of SF are promoted by the natural formation of β-sheet crystals where the mechanical characteristics can be tuned by inducing β-sheet formation. , However, encapsulating cells with pristine SF is challenging as SF has a net negative charge, and the membrane resting potential of the cell is usually negative. , Silk has been chemically modified by incorporating sufficient net charge to deposit silk through electrostatic LbL to overcome this drawback. By coupling silk fibroin with poly lysine hydrobromide (PL) and poly glutamic (PG) acid sodium salts, silk ionomers have been synthesized previously and used for successful encapsulation. , However, these coating materials are not compatible with mammalian cells due to their higher charge density, making them cytotoxic.…”
Section: Introductionmentioning
confidence: 99%